2011
DOI: 10.1177/0194599811400366
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroid Parathyroid Adenoma

Abstract: The incidence of true iT-PA is less than 1%, occurring in predictable locations. Thyroid lobectomy for a missing parathyroid adenoma is typically unsuccessful and should only rarely, if ever, be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Different literatures have reported that the incidence rate of ETPA is 0.2% to 6.0%. [57] Cystic parathyroid adenomas take up 1% to 2% [4] of PHPT cases. Colsa-Gutiérrez et al [8] considered that cystic parathyroid adenomas could be caused by embryological remnants of the 3rd or 4th pharyngeal pouches and preservation of glandular secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Different literatures have reported that the incidence rate of ETPA is 0.2% to 6.0%. [57] Cystic parathyroid adenomas take up 1% to 2% [4] of PHPT cases. Colsa-Gutiérrez et al [8] considered that cystic parathyroid adenomas could be caused by embryological remnants of the 3rd or 4th pharyngeal pouches and preservation of glandular secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evaluating radiologist should search for radiological manifestations of hyperparathyroidism, such as osteopenia, bone resorption, and brown tumours (Fig. 22 ) [ 55 , 56 ].
Fig.
…”
Section: Intra-thyroid Parathyroid Adenomamentioning
confidence: 99%
“…As shown in postmortem studies, the incidence of the intra-thyroid location of the parathyroid glands was estimated at less than 0.2%, and 2–5% in PH patients (17) . The same rate was estimated as less than 1% in a retrospective study by Goodman including more than 10,000 patients (18) . Intrathyroidal adenomas are difficult to distinguish from lesions that are typically visualized on ultrasound in the course of thyroid goiter.…”
Section: Ultrasonographymentioning
confidence: 88%